2017
DOI: 10.1088/1748-0221/12/12/p12016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Goubau line for testing beam diagnostic instruments

Abstract: A: One of the main characteristics of the Goubau line is that it supports a low-loss, nonradiated surface wave guided by a dielectric-coated metal wire. The dominant mode of the surface wave along the Goubau line is a TM 01 mode, which resembles the pattern of the electromagnetic fields induced in the metallic beam pipe when the charged particle beam passes through it. Therefore, the Goubau line can be used for the preliminary bench test and performance optimization of the beam diagnostic instruments without r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…These findings are consistent with the simulation results of Ref. [19], who found that the wire needs to be sufficiently long to insure good launching and receiving efficiency. This is because the G-line needs sufficient space between the cones and the DUT for the surface waves to fully develop.…”
Section: B Description Of the G-line Setup Designed At Argonne Natiosupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with the simulation results of Ref. [19], who found that the wire needs to be sufficiently long to insure good launching and receiving efficiency. This is because the G-line needs sufficient space between the cones and the DUT for the surface waves to fully develop.…”
Section: B Description Of the G-line Setup Designed At Argonne Natiosupporting
confidence: 92%
“…The G-line has been used by several groups to characterize beam position monitors (BPMs) and current transformers [15,17,19,26]. Simulations showing the G-line's potential to assess vacuum component impedance were described in Refs.…”
Section: Goubau-line (G-line)mentioning
confidence: 99%
See 2 more Smart Citations